The Effects of Social Engagements to the Academic Pursuits on Nursing Students - Dy, Mizaki Alexza; Bactol, Charlotte; Dacera, Divine; Payumo, Mary Agnes; Raguindin , Sandhie; Tayo , Ica Ella; Merced, Joel John Dela; Sedeno , Carlos Kurt; Salcedo , Trinidad J.; Jecino , Liza May B.; Palig-ad, Abigail P.; Pambuan , Susana; Abonalla , Arby James; Aggari , Michael (Celebes Nursing Journal, 2025)
This study investigates how social engagement impacts third-year nursing students' academic performance and well-being. While social support benefits academic engagement, more research is needed on nursing students’ unique challenges and social experiences. This quantitative correlational study investigated the relationship between social engagements and academic achievements among third-year students. Data were collected through face-to-face surveys using Likert scale questions from 306 participants at a prominent school in Quezon City. Purposive sampling was employed, focusing on students involved in extracurricular activities. Findings revealed that majority of respondents were 21 years old (55.23%), predominantly female (73.86%), and had a weekly allowance below PHP 1,000 (51.31%). Social engagements was generally low, with the highest participation in birthday celebrations (mean: 3.085, "Moderately Engaged") and the lowest in dance troupe activities (mean: 1.428, "Not Engaged at All"). Despite low engagement, students perceived social interactions as beneficial, enhancing academic satisfaction (mean: 3.159, "Agree"), cognitive function (mean: 3.189, "Agree"), and mental health (mean: 3.25, "Agree"). A weak positive correlation was found between social engagement and academic performance (Pearson R = 0.340, p < 0.001). The findings concluded that even limited social interactionl benefits nursing students. To balance academics and social life, researchers recommended promoting extracurricular clubs and wellness programs, acknowledging the importance of social connections for academic success.